User Experience and User Satisfication Analysis of Learning Assistance Services (Tuweb, Tuton, TMK) at UPBJJ-UT Bengkulu - Mikaresti, Pamela; Yusrizal, Yusrizal; Nurmalia, Ana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to analyze user experience and user satisfaction for learning assistance services, namely web-based tutorials, online tutorials and course assignments. The research method used is descriptive quantitative. The number of samples is 540 respondents, namely students. The instrument used is a questionnaire which is shared with google form. The data analysis technique of this research uses the Likert scale method and multiple linear regression. The results showed that the three learning aid services had positive user experience and user satisfaction. More than 75% of respondents rated the user experience and user satisfaction of TUWEB, TUTON and TMK as being in the good and high categories. TUWEB, TUTON and TMK study assistance services are available to meet the needs of various students. Students who like to study more intensely, can interact virtually in two directions via video conferencing will choose TUWEB. Students who find it difficult to find a scheduled time and prefer to study with a more flexible but still focused time will choose TUTON. As for students who do not want to take part in TUWEB or TUTON, there is a more practical TMK. Variables that have a significant effect on user satisfaction of TUWEB learning aid services are dependability and stimulation. Variables that have a significant effect on user satisfaction of TUTON learning aid services are attractiveness, perspicuity and stimulation. Variables that have a significant effect on user satisfaction of TMK learning aid services are efficiency and novelty.